2017
DOI: 10.1259/bjr.20170241
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent weekly cisplatin versus triweekly cisplatin with radiotherapy for locally advanced squamous-cell carcinoma of the cervix: a retrospective analysis from a single institution

Abstract: Objective:To compare patients with cervical cancer who were primarily treated with concurrent chemoradiotherapy (CCRT) using 20 mg m−2 CDDP for 5 days every 3 weeks with weekly regimens of 40 mg m−2.Methods:We retrospectively analyzed 185 patients with Stage IB–IVA squamous-cell carcinoma of the cervix who were treated with CCRT between 2005 and 2013 at our hospital. The CCRT regimen consisted of cisplatin (CDDP) at 20 mg m−2 for 5 days every 3 weeks or 40 mg m−2 weekly, administered concomitantly with RT.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… 11 Conversely, outcomes of weekly CDDP regimen for CCRT were found to be better with respect to hematological toxicity in a study conducted by Kinjyo et al in 2017. 12 No definitive conclusions were drawn from these studies. Therefore, 6 randomized trials and 2 retrospective studies were included in our meta-analysis to explore the difference between the different CDDP-alone regimens for patients with LACC.…”
Section: Introductionmentioning
confidence: 90%
“… 11 Conversely, outcomes of weekly CDDP regimen for CCRT were found to be better with respect to hematological toxicity in a study conducted by Kinjyo et al in 2017. 12 No definitive conclusions were drawn from these studies. Therefore, 6 randomized trials and 2 retrospective studies were included in our meta-analysis to explore the difference between the different CDDP-alone regimens for patients with LACC.…”
Section: Introductionmentioning
confidence: 90%
“…Akin retrospective study by Kinjyo et al reported no significant difference in OS, DFS and distant DFS. The 5-year DFS was 88.5% and 87.9% and distant DFS was 83.9% and 84.1% in the triweekly and weekly arm (p = 0.782 and p = 0.938), respectively (18). Kinjyo used a similar protocol as Nagy et al A 2-year complete response of 95.1% and 87.8% in tri-weekly and weekly arms were proclaimed by Panda et al The three-weekly arm used 75 mg/m 2 unlike our study which used 100 mg/m 2 .…”
Section: Discussionmentioning
confidence: 94%
“…122,123 and a retrospective single-institution review. 124 The conclusions from these studies are blurred because of the inclusion of both singleagent cisplatin and mostly combination regimes in a triweekly arm and the inclusion of retrospective studies with adjuvant CTRT in patients postoperatively. 122,123 The safety and efficacy of CTRT(3wkly Pt) over CTRT(wkly Pt) has been demonstrated in 3 randomized trials in LACC.…”
Section: Discussionmentioning
confidence: 99%